Pembuatan Media Pembelajaran Instalasi Penerangan Listrik Berbasis Android - Rio Julian; Mukhlidi Muskhir; Afdal Lutfhi (Jurnal Pendidikan Teknik Elektro, 2023)
Purpose of Making Android-based Learning Media using ispring suite on electrical lighting installation materials to produce valid Android-Based Learning Media. The application was made using the 4-D development model research method), respondents to media expert lecturers from the department of electrical engineering, Faculty of Engineering, Padang State University, and teachers of class XI TITL at SMK Negeri 5 Padang. The research instrument is a learning media validation questionnaire. Results response analysis show that the validation of each validator is declared valid, thus the Android-Based Electric Lighting Installation Learning Media using the Ispring Suite application is declared valid as a learning media that is worth using.